PERFORMANCE ANALYSIS OF COSTS AND TIME WITH THE CONCEPT OF EARNED VALUE ANALYSIS ON BUILDING CONSTRUCTION PROJECT - ROEM, NAS (KURVA S JURNAL MAHASISWA, 2014)
Controlling a project is a stage that plays an important role in the process of achieving the goal of a construction project. The purpose of control is to monitor, assess, holding and guiding corrections that can be done that has been established in accordance with the plan. One method used is the concept of Value Method Results (earned Value Concept). Besides being able to know the status of the project cost and time, concept of value method can also predict the results of future projects. This method combines the concept of value results of three elements, namely elements of cost, schedule elements and physical elements of the work.This study takes an object on Palm Oil Mill Development Project located in the village of Batu Lepoq District of Authorship East Kutai Regency of East Kalimantan Province, conducted by PT. Prima Indah Perwita. From the results of the evaluation and analysis of the data obtained the status of the cost and time of reporting, the construction work of the main office, to the value of the cost performance index (CPI) and a performance index (SPI) at week 8 were 0,77 and 0,69, this shows that the costs were greater than the value of the budget as well as menagalami delays in implementation. The expected costs required by the end of the project is Rp 818.85. 460, - and the implementation time is 47 weeks. In this case the executor of a loss of Rp 7,042,591, - (0,87% of the budget).Â